The Effect of Magnesium Variation on the Hardness Characteristics of Aluminium/SiC/Rice Husk Ash Composites - M Cakra Putra Prakarsa; M Prama Diva Liza; Amir Arifin; Nanda Yusril Mahendra; Muhammad Rizky Tolusha Putra; M Widy Prabowo Trilaksono; Hasan Basri (International Journal of Mechanics, Energy Engineering and Applied Science (IJMEAS), 2026)
The reutilization of aluminum scrap as a composite matrix is an effective strategy to reduce import dependence and environmental impact, yet recycled aluminum typically exhibits inferior mechanical properties, requiring additional reinforcement. This study investigates the effect of varying weight fractions of the wetting agent magnesium (Mg) on the hardness characteristics of Aluminum Matrix Composites (AMCs) reinforced with sustainable Silicon Carbide (SiC) and Rice Husk Ash (RHA). The composites were fabricated using the stir casting method with fixed reinforcement contents of 2 wt% SiC and 2 wt% RHA, while Mg was varied at 0 g (control), 1.0 g (1 wt%), and 1.5 g (1.5 wt%). Hardness testing was performed using the Rockwell method (HRF scale). The results show that Mg addition significantly improves hardness compared to pure aluminum. The average hardness increased from 65.5 HRF for pure aluminum to 64.4 HRF with 1.0 wt% Mg and reached an optimum value of 69.1 HRF at 1.5 wt% Mg. The improvement is attributed to Mg enhancing wettability and strengthening interfacial bonding between the aluminum matrix and reinforcement particles, effectively impeding dislocation movement. It is concluded that 1.5 wt% Mg provides the optimal hardness enhancement for Aluminum/SiC/RHA composites produced via stir casting.